The Extinction Rebellion and going beyond politics: can deliberation be the answer in climate mitigation? - Janette Huttunen (Fennia: International Journal of Geography, 2024)
The United Nations (UN) has characterized the climate crisis as ‘the defining crisis of our time’ (United Nations 2023). To address the crisis in the 2020s, the so-called new climate movement has emerged to protest the inadequate climate action taken by political power holders and to demand real political action on climate issues. One of the movement’s branches is Extinction Rebellion, which has three central demands: demand for the government to ‘act now’ (to halt biodiversity loss and reduce greenhouse-gas emissions to net zero by 2025), to ‘tell the truth (by declaring climate emergency) and to ‘go beyond politics’ by introducing a Citizens Assembly on climate and environmental justice. The question, however, is how impactful these demands, and by extension, actions, can be to address the issue of the climate crisis. This Reflection takes a critical view of Extinction Rebellion’s third goal, going beyond politics, and discusses the potential issues with the impact of the proposed Climate Assembly.